Michael Chiago : O'odham Lifeways Through Art - Rea, Amadeo M. (Book collections on Project MUSE., 2022)
"O'odham artist Michael Chiago Sr.'s paintings provide a window into the lifeways of the O'odham people. This book offers a rich account of how Tohono O'odham and Akimel O'odham live in the Sonoran Desert now and in the recent past"--